2005
DOI: 10.1074/jbc.m413090200
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Neuronal Calcium Sensor-1 and ADP-ribosylation Factor 1 Allows Bidirectional Control of Phosphatidylinositol 4-Kinase β and trans-Golgi Network-Plasma Membrane Traffic

Abstract: We have identified a novel Ca 2؉ -dependent interaction between neuronal calcium sensor-1 (NCS-1) and the GTPase ARF1. Both of these proteins are localized to the Golgi complex, and both regulate phosphatidylinositol 4-kinase III␤ (PI(4)K␤). Spatial and temporal control of phosphatidylinositol 4-phosphate levels through activation of PI(4)K␤ is important for the recruitment of trafficking complexes to the trans-Golgi network (TGN) and vesicular traffic from this organelle. The NCS-1-ARF1 interaction and its sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
129
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(140 citation statements)
references
References 54 publications
7
129
4
Order By: Relevance
“…To next address the question of which functional consequences calneuron-1 binding might have for PI-4K␤'s enzymatic activity we performed in vitro kinase assays with bacterially-expressed proteins. Conflicting evidence exists whether myristoylated NCS-1 activates PI-4K␤ in vitro in a Ca 2ϩ -dependent manner and whether the interaction by itself is Ca 2ϩ -independent (11,19). We found that the basal activity of the kinase was unaltered in the presence of myristoylated NCS-1 when Ca 2ϩ was omitted from the buffer (Fig.…”
Section: Calneuron-1 Regulates Pi-4k␤ Activity In a Ca 2؉ -Dependent mentioning
confidence: 55%
See 1 more Smart Citation
“…To next address the question of which functional consequences calneuron-1 binding might have for PI-4K␤'s enzymatic activity we performed in vitro kinase assays with bacterially-expressed proteins. Conflicting evidence exists whether myristoylated NCS-1 activates PI-4K␤ in vitro in a Ca 2ϩ -dependent manner and whether the interaction by itself is Ca 2ϩ -independent (11,19). We found that the basal activity of the kinase was unaltered in the presence of myristoylated NCS-1 when Ca 2ϩ was omitted from the buffer (Fig.…”
Section: Calneuron-1 Regulates Pi-4k␤ Activity In a Ca 2؉ -Dependent mentioning
confidence: 55%
“…Moreover, its binding to PI-4K␤ seems to be of lower affinity as compared with the yeast proteins (11). It is therefore likely that the regulation of Pik1 and PI-4K␤ differs substantially with the latter being more susceptible to modulation via Ca 2ϩ transients at the Golgi (19).…”
mentioning
confidence: 95%
“…Recently, it has been shown that PITP␤ is needed for the vesicular transport at the Golgi (20). In this case, the authors suggested that PITP␤ is needed to bring PI to the Golgi for the synthesis of phosphatidylinositol 4-phosphate, which is involved in vesicular trafficking at the Golgi (21).…”
Section: Dagmentioning
confidence: 99%
“…NCS-1 can also interact with the mammalian Golgi enzyme PI4KIIIb and enhances its activity three-to 10-fold (Taverna et al 2002;Haynes et al 2005;de Barry et al 2006). The interaction with Golgi-associated PI4KIIIb suggests that it may regulate secretion through the modulation of phosphatidylinositol-dependent trafficking steps (Hendricks et al 1999;Zhao et al 2001;Haynes et al 2005). In support of this, NCS-1 has also been demonstrated to associate with another PI4KIIIb regulator ARF1, a small GTPase critical to multiple trafficking steps in mammalian cells Haynes et al 2007).…”
Section: Calcium Sensor Proteins In Neuronal Functionmentioning
confidence: 99%